Preparation, Characterization and Antibacterial Activity of Blueberry Pomace Polyphenol-Selenium Nanoparticles - XU Yaqin, ZHONG Jingwei, LI Guoqiang, WANG Xinru, CHANG Songtao, YANG Yu, WANG Libo (Shipin Kexue, 2023)
Total polyphenol-selenium nanoparticles (TP-SeNPs) were prepared with blueberry pomace polyphenols, prepared by ultrasonic assisted aqueous two-phase extraction and purified by using macroporous resin X-5. The structure of TP-SeNPs was characterized by energy dispersive X-ray (EDX) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM) and X-ray diffraction (XRD), and the antibacterial activity was measured. The results showed that selenium salt was reduced into elementary selenium, and hydrogen bond-like interactions existed between the O–H groups of polyphenols and nanoselenium atoms. Additionally, TP-SeNPs were stable as an amorphous solid which was nearly spherically dispersed. The inhibitory effect of TP-SeNPs was better against Gram-positive bacteria than against Gram-negative bacteria. The minimum inhibitory concentration (MIC) against Listeria monocytogene was 0.06 mg/mL. TP-SeNPs effectively inhibited the formation of L. monocytogene biofilms, and destroyed the permeability and integrity of the cell wall and membrane, and caused leakage of cell contents, thereby leading to the death of L. monocytogene. This study offers a new idea for the application of blueberry pomace and selenium nanoparticles, and provides a theoretical basis for the development of selenium nanoparticles with antimicrobial activity.